Herpetofauna de uma área de Caatinga em Taquaritinga do Norte, Agreste de Pernambuco, Brasil - Barbosa, Vanessa N. (2018)
The objective of this research was to make an inventory of the herpetofaunal community of a Caatinga region from Boa Vista’s farm, in Taquaritinga do Norte, Pernambuco state, Brazil. We collected field data from August 2013 to July 2014 using diverse sampling methods: time-limited visual searches, pitfall trapping, record of vestiges and occasional encounters by local people. We could detect the presence of 42 species, 17 amphibians, and 25 reptiles. Rhinella jimi, Tropidurus semitaeniatus and Tropidurus hispidus were apparently the most abundant. The most efficient sampling method was time-limited visual searches, which allowed the record of 34 species. The species composition of the studied community is similar to other Caatinga areas in the state of Pernambuco. We highlight the importance of weirs and similar man-made habitats that provide shelter and reproduction, especially for anurans.